(untitled) (Analytical Methods for Drug Development, 2025)
Author Miss Aastha Sharma Assistant Professor, SD College of Pharmacy & Vocational Studies, Muzaffarnagar, Uttar Pradesh, India Abstract Dissolution testing measures the rate and extent of drug release from pharmaceutical dosage forms. USP apparatus types 1-7 simulate in-vivo conditions with specific designs for various dosage forms, each requiring proper calibration and qualification. Method development considers media composition including pH, buffer capacity, and surfactants alongside hydrodynamic conditions, sampling strategies, and analytical finish methods. Immediate release, modified release, and poorly soluble drug formulations require tailored dissolution approaches. Data analysis applies model-dependent approaches using zero-order, first-order, and Higuchi equations alongside model-independent methods like dissolution efficiency and similarity factors. Mathematical modeling enables profile comparison and discrimination with statistical significance testing. Regulatory agencies establish method validation requirements, acceptance criteria, and specification setting practices globally. In vitro-in vivo correlation links dissolution behavior to pharmacokinetic parameters through levels A-C correlations, supporting biowaivers, formulation optimization, and specification setting. Keywords: Dissolution Profile, Biorelevant Dissolution Media, Modified Release Testing, In-Vitro In-Vivo Correlation VIEW PDF